2022
DOI: 10.3390/su15010688
|View full text |Cite
|
Sign up to set email alerts
|

The Influencing Factors of Pro-Environmental Behaviors of Farmer Households Participating in Understory Economy: Evidence from China

Abstract: To promote the sustainable development of agriculture and forestry economy, it is of great significance to guide farmers to consciously pursue pro-environmental behaviors in the development of the understory economy. Based on field survey data from Yong’an city of Fujian Province and Luoshan County of Henan Province, factor analysis and Oprobit models were mainly used to analyze the influencing factors and influencing the degree of the pro-environmental behaviors of farmer households participating in the under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Developing comprehensive subsidy application procedures and requirements and strict supervision of the use of funds will ensure that enterprises use them for innovation in green technology [107,108]. Expand the financing channels for corporate environmental investment, minimize financing risks and financing constraints, lower the cost of financing for corporate environmental investment, and assist businesses in overcoming the cash flow shortage that constrains corporate environmental investment [109]. Simultaneously, the active use of economic and incentive-based policies, the development of incentives and voluntary policies to strengthen the "inherent constraints" of social and economic development, to encourage carbon capture listed companies to explore newly available resources, the result of new materials utilization, clean production technologies, and environmental pollution control technologies, to steer the transformation of carbon capture technology and industry.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…Developing comprehensive subsidy application procedures and requirements and strict supervision of the use of funds will ensure that enterprises use them for innovation in green technology [107,108]. Expand the financing channels for corporate environmental investment, minimize financing risks and financing constraints, lower the cost of financing for corporate environmental investment, and assist businesses in overcoming the cash flow shortage that constrains corporate environmental investment [109]. Simultaneously, the active use of economic and incentive-based policies, the development of incentives and voluntary policies to strengthen the "inherent constraints" of social and economic development, to encourage carbon capture listed companies to explore newly available resources, the result of new materials utilization, clean production technologies, and environmental pollution control technologies, to steer the transformation of carbon capture technology and industry.…”
Section: Policy Implicationsmentioning
confidence: 99%
“…2.3.3 Social pressure. Social pressure can significantly shape an individual's intentions and behaviors related to sustainability (Chen et al, 2023). Research has shown that social pressure can positively impact sustainable behavioral intention, meaning that individuals are more likely to engage in sustainable behaviors when they feel pressure from their social group (Van Tonder et al, 2023).…”
Section: Environmental Knowledgementioning
confidence: 99%
“…Social pressure can influence sustainable behavior in several ways, one of which is the concept of social norms (Gleim et al, 2013). Social norms refer to the unwritten rules and expectations that govern how people behave in a given group or society (Chen et al, 2023). When individuals see their peers engaging in sustainable behaviors, they may feel pressure to conform to these norms and adopt similar behaviors (Gleim et al, 2013).…”
Section: Environmental Knowledgementioning
confidence: 99%
See 2 more Smart Citations